Արթուր Մկրտչյանի դերը Արցախի ազգային-ազատագրական պայքարում - Բալայան, Ռոնա
Основным стерженем данной статьи является роль представителя нового поколения борцов за национально-освободительные идеи Артура Аслановича Мкртчяна, который, следуя лучшим традициям предков, продолжал неустанную борьбу за освобождение Арцаха. В статье особо выделены организаторская и боевая деятельность Артура Мкртчяна в оказавшем в тяжелом положении Гадруте, а также освещено его служение народу на посту первого президента НКР, его политические и дипломатические заслуги. The main core of this article is the role of the representative of a new generation of fighters for national liberation ideas Arthur A. Mkrtchyan who following the best traditions of their ancestors, continued tireless struggle for the liberation of Artsakh. The article highlighs organizational and combat activities of Arthur Mkrtchyan in Hadrout which was in difficult situation at that period, and lights up his serving to his people on the post of the first President of the NKR, his political and diplomatic achievements.
Keywords: Ազգային-ազատագրական շարժումը Արցախում